A mosaic mutation in the CLCNKB gene causing Bartter syndrome: A case report - Zhou, Lan; Chen, Xiaohui; Xiong, Jiaojiao; Lei, Ling (Frontiers in Pediatrics, 2023)
Abstract Background Type III Bartter syndrome (BS) is an autosomal recessive disease caused by mutations in CLCNKB (chloride voltage-gated channel Kb) gene which encodes CLC-Kb. CLC-Kb is mainly located in the thick ascending limb of Henle’s loop and regulates chloride efﬂux from tubular epithelial cells to the interstitium. Type III BS is characterized by metabolic alkalosis, renal salt wasting, hyperreninemic, and hyperaldosteronism with normal blood pressure. Case presentation We reported a 3-day-old girl whose initial symptom was jaundice but accidentally found metabolic alkalosis. She showed recurrent metabolic alkalosis, hypokalemia, and hypochloremia and also had hyperreninemic and hyperaldosteronism with normal blood pressure. Potassium infusion therapy and oral potassium supplement were not able to completely reverse electrolytes disturbance. She was suspected of Bartter syndrome and genetic tests were performed on her and her parents. Next-generation sequencing identified CLCNKB gene mutation including heterozygous mutation c.1257delC (p.M421Cfs*58) and a low-level mutation c.595C>T (p.E199*), both mutations were verified in the parents respectively. Conclusion We reported a classic Bartter syndrome in a newborn with a heterozygous frameshift mutation and a low variant allele frequency nonsense mutation on the CLCNKB gene.